Palæomagnetism of Certain Rocks from Newfoundland (Dataset) ... - A. E. M. NAIRN; D. V. FROST; B. G. LIGHT (Magnetics Information Consortium (MagIC), 2006)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Palæomagnetism of Certain Rocks from Newfoundland ...